THE EFFECT OF JOB INSECURITY AND JOB SATISFACTION ON TURNOVER INTENTION OF CONTRACT EMPLOYEES AT PT ADETEX BANJARAN - Kristin Nurhayati; Dadang Munandar (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the effect of job insecurity and job satisfaction on the turnover intention of contract employees at PT Adetex Banjaran. Employment conditions in the textile industry indicate a relatively high level of job uncertainty, particularly for contract employees who experience changes in work schedules, income fluctuations, and limited guarantees of job continuity. These conditions have the potential to reduce job satisfaction and encourage employees’ intention to leave the company. This research employs a quantitative approach using a survey method. The research population consists of all contract employees at PT Adetex Banjaran, with the sample determined using a proportional sampling technique. Data were collected through the distribution of questionnaires developed based on indicators of job insecurity, job satisfaction, and turnover intention. Data analysis was conducted using descriptive and inferential statistical techniques with the assistance of SPSS software, including validity and reliability tests, classical assumption tests, correlation analysis, multiple linear regression analysis, coefficient of determination, and partial and simultaneous hypothesis testing. The results indicate that job insecurity has a positive and significant effect on turnover intention, meaning that the higher the level of job insecurity perceived by employees, the greater their tendency to leave the company. In addition, job satisfaction has a negative and significant effect on turnover intention, indicating that higher job satisfaction leads to a lower intention to leave the organization. Simultaneously, job insecurity and job satisfaction have a significant effect on the turnover intention of contract employees at PT Adetex Banjaran. These findings highlight the importance of human resource management practices that focus on enhancing job security and job satisfaction in order to reduce turnover intention. This study is expected to serve as a consideration for company management in formulating more stable, fair, and sustainable employment policies, as well as a reference for future research in the field of human resource management.